PENGARUH KESELAMATAN DAN KESEHATAN KERJA (K3) DAN MOTIVASI KERJA TERHADAP PRODUKTIVITAS KERJA (STUDI KARYAWAN BAGIAN PRODUKSI PADA PT. RAMAJAYA PRAMUKTI PETAPAHAN, KAB. KAMPAR) - Rani Angelina Pandiangan; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study aims to determine the application of occupational safety and health (OHS) and work motivation to work productivity of production employees at PT. Ramajaya Pramukti Petapahan, Kampar Regency. Occupational safety and health (OHS) and work motivation as independent variables (X1X2) while work productivity as the dependent variable (Y). This research was conducted at PT. Ramajaya Pramukti Petapahan, Kampar Regency, located at Raya Petapahan street, km 27, Kampar, Riau. The research method used is quantitative descriptive analysis. Data obtained from secondary data by the company and primary data through questionnaire measured by a likert scale then processed with SPSS version 22. The sample of this study was 60 respondents. The data analysis technique in this study used simple linear regression and multiple linear regression analysis.            The result showed that occupational safety and health (OHS) had an effect on work productivity with a value of t count > t table (12.270 > 2.00172) and significance (0.000 < 0.05). work motivation has an effect on work productivity with t value > t table (10.579 > 2.00172) and significance (0.000 < 0.05). Occupational safety and health (OHS) and work motivation affectape productivity with F value > F table (101.176 > 3.16) and significance (0.000 < 0.05). It can be concluded that occupational safety and health (OHS) and work motivation simultaneously have a significant and positive effect on the work productivity of employees at PT. Ramajaya Pramukti Petapahan, Kampar Regency. Keywords: Occupational Health and Safety, Motivation, Productivity